Diagnostic Delay in Ankylosing Spondylitis: Related Factors and Prognostic Outcomes - Sasan FALLAHI,; Ahmad Reza JAMSHIDI, (Archives of Rheumatology, 2016)
Objectives: This study aims to evaluate diagnostic delay, factors which are related to diagnostic delay, and the effect of diagnostic delay on prognostic outcomes in terms of spinal and hip mobility, functional status, disease activity, quality of life, cervical rotation, tragus to wall distance, and sacroiliitis severity in an Iranian population with ankylosing spondylitis (AS). Materials and methods: One hundred and sixty three patients (129 males, 34 females; mean age 37.74±9.88 years; range 18 to 65 years) with AS who met modified New York 1984 criteria were enrolled consecutively in a cross sectional survey. The main outcome variable (diagnostic delay) was defined as the interval between appearance of first symptoms and correct diagnosis of AS. Enthesitis, negative human leukocyte antigen B27 (HLA- B27), and educational level were among the factors of which their relationship to diagnostic delay were evaluated. The prognostic outcomes were measured using Bath ankylosing spondylitis functional index, Bath ankylosing spondylitis disease activity index, AS quality of life, Bath ankylosing spondylitis metrology index, chest expansion, and radiographic sacroiliitis severity. Results: Diagnostic delay was mean 7.88±7.17 years. Diagnostic delay was longer in patients with enthesitis (8.80±7.27) compared to patients without enthesitis (6.04±6.66) (p=0.007) and in HLA-B27 negative patients (10.10±7.44) compared to HLA-B27 positive patients (7.14±6.96) (p=0.013). Educational level was negatively correlated with diagnostic delay (p=0.002, r= -0.24). Diagnostic delay was correlated with Bath ankylosing spondylitis functional index (p=0.003, r=0.23), Bath ankylosing spondylitis disease activity index (p=0.026, r=0.18), AS quality of life (p=0.008, r=0.21), Bath ankylosing spondylitis metrology index (p<0.001, r=0.41), chest expansion (p<0.001, r= - 0.38), and sacroiliitis grading (p=0.042, r=0.16). Conclusion: Negative HLA-B27, enthesitis, and low educational level are factors which affect diagnostic delay in AS. Individuals with enthesitis or low educational level should be evaluated accurately without causing delay in diagnosis since longer delay may lead to poorer prognostic outcomes.